2021
DOI: 10.3390/coatings11070861
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on Gold-Like Luster Development of Solution-Cast Oligo(3-methoxythiophene) Film

Abstract: Solution-cast coating films of perchlorate-doped oligo(3-methoxythiophene) exhibited a gold-like luster similar to that of metallic gold despite the involvement of no metals. However, the development mechanism of the luster remains ambiguous. To understand the mechanism, we performed scanning electron microscopic analysis, variable-angle spectral reflectance measurements, and ellipsometry measurements on ClO4−-doped oligo(3-methoxythiophene) cast film with a gold-like luster. The results revealed that the lust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…We note that differences in film thickness of about 1 to 3 μm did not affect the measurement of optical constants. The spectral shapes of n and κ for Films - 2 – 7 are similar to those for Film-1 and our previously reported Cl – -doped 3-methoxythiophene oligomers. The n value increased sharply from approximately 500 to 600 nm and continued to increase moderately from approximately 700 nm. The κ value increased at a wavelength 50 nm shorter than n , reaching a maximum between 600 and 700 nm and gradually decreasing afterward.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We note that differences in film thickness of about 1 to 3 μm did not affect the measurement of optical constants. The spectral shapes of n and κ for Films - 2 – 7 are similar to those for Film-1 and our previously reported Cl – -doped 3-methoxythiophene oligomers. The n value increased sharply from approximately 500 to 600 nm and continued to increase moderately from approximately 700 nm. The κ value increased at a wavelength 50 nm shorter than n , reaching a maximum between 600 and 700 nm and gradually decreasing afterward.…”
Section: Resultssupporting
confidence: 84%
“…Based on our previous studies, we can conclude that the glossy appearance of Film-1 is due to the compact lamellar crystallites formed by the 3-methoxythiophene oligomer chains in the film. These crystallites exhibited very large optical constants, as shown in Figure . Although the specular refraction spectra of Film-1 and the vacuum-deposited gold film appear similar, the n and κ characteristics and mechanisms that produce the reflections differ.…”
Section: Resultsmentioning
confidence: 83%
“…These colorimetric results are consistent with the results of the reection spectral measurements. In our previous studies, [17][18][19][20][21][22][23] we found that two types of crystallites are present in the solution-cast lms of O3MeOT, namely edge-on lamellar crystallites formed by the stacking of thiophene rings oriented perpendicular to the substrate (Fig. 4a), and face-on lamellar crystallites formed by the stacking of thiophene rings oriented parallel to the substrate (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Such methods include crystallization, [3][4][5][6][7][8] solidication by ltration, [9][10][11][12] electrochemical polymerization, [13][14][15][16] and solution application. [17][18][19][20][21][22][23] However, the design of a novel and more facile method for the development of metallic lusters could promote the application of the corresponding organic materials in the eld of decoration, while also expanding their range of uses.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the smooth surfaces of organic crystals and polymer films sometimes display strong noniridescent specular reflection and thus invoke a metallic luster. , Recently, Hoshino and coworkers established judicious manipulation of polythiophene films to faithfully imitate golden luster. Noble metallic luster from crystals of alkylated mesogenic compounds, such as azobenzene and stilbene, is demonstrated by Kondo and coworkers. In these cases, the metal-lustrous color mirrors the electronic structures of the organic compounds. Overlooking the theoretical establishment by Anex and Simpson in 1960, the noniridescent surface metallic reflection of organic materials had been phenomenologically reported until Kanbara and coworkers reported that the reflection spectrum of the smooth surface of the polymer film reliably agrees with the chromatic dispersion of the refractive index …”
Section: Introductionmentioning
confidence: 99%